ATTITUDE OF TET AMONG B.ED. STUDENT-TEACHERS - Christina, A. Daisy (International Journal of Research -GRANTHAALAYAH, 2016)
Teacher Eligibility Test is an Indian entrance examination for teachers. The test is mandatory for getting teaching jobs in government schools from Class 1 to Class 8. Paper 1 is meant for teachers opting for Class 1 to Class 5 and Paper 2 for Class 6 to Class 8. It is conducted by both Central government and State governments in India. Most states conduct their own TET. The present study focused on the positive and negative attitudes towards TET examination. For this purpose, this research was conducted with 500 student teachers in survey method. A self-made tool consists of 27 items. The findings of this study brought into light some vital reasons behind the attitudes exhibited by the teachers regarding TET, was mainly due to the importance of TET, its necessity, and the problems faced by the teachers while attending TET. On the basis of the findings it is suggested that, as the test is mandatory for getting teaching jobs in government schools, all the opportunities, resources and facilities should be given to the student teachers during their B.Ed. course for their professional development and to fulfill and achieve educational goals. It is necessary to ensure teachers with the essential aptitude and ability to meet the challenges of teaching at the primary and upper primary level.